2017
DOI: 10.1021/acs.organomet.6b00895
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium and Iridium Dipyridylamine Catalysts for the Efficient Synthesis of γ-Valerolactone by Transfer Hydrogenation of Levulinic Acid

Abstract: International audienceThe selective and efficient transfer hydrogenation of levulinic acid into γ-valerolactone was performed with new ruthenium and iridium catalysts bearing dipyridylamine (dpa) ligands. Reactions were performed in the presence of formic acid and triethylamine using catalyst loading as low as 0.05 mol % with a ruthenium complex (turnover number = 1980). Recyclability of a ruthenium catalyst was demonstrated by running 6 consecutive reactions in almost quantitative yields

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…We evaluated a series of air‐ and moisture‐stable iridium and ruthenium complexes (Figure ) that have not been previously used for the hydrogenation of HMF to HHD. The best results were obtained with the half‐sandwich [Cp*Ir(dpa)Cl]Cl (dpa=dipyridylamine) catalyst I (Table , entry 1), which is a known catalyst for water oxidation and the transfer hydrogenation of levulinic acid . Poor selectivities were observed with ruthenium complexes II , IV , and V (Figure and Table , entries 2, 4, and 5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated a series of air‐ and moisture‐stable iridium and ruthenium complexes (Figure ) that have not been previously used for the hydrogenation of HMF to HHD. The best results were obtained with the half‐sandwich [Cp*Ir(dpa)Cl]Cl (dpa=dipyridylamine) catalyst I (Table , entry 1), which is a known catalyst for water oxidation and the transfer hydrogenation of levulinic acid . Poor selectivities were observed with ruthenium complexes II , IV , and V (Figure and Table , entries 2, 4, and 5).…”
Section: Methodsmentioning
confidence: 99%
“…The best resultsw ere obtained with the half-sandwich [Cp*Ir(dpa)Cl]Cl (dpa = dipyridylamine) catalyst I ( Table 1, entry 1), which is ak nown catalyst for water oxidation [13] and the transfer hydrogenation of levulinic acid. [14] Poor selectivities were observed with ruthenium complexes II, IV,a nd V (Figure1 and Ta ble1,e ntries 2, 4, and 5). After fur- ther optimization,t he best resultsw ere obtained with I (0.5 mol %) with 10 bar H 2 at 120 8Ci nw ater and HHD was isolated in 69 %y ield ( Table 1, entry 1).…”
mentioning
confidence: 96%
“…Recently, our group has been investigating the reduction of levulinic acid into γ‐valerolactone by using ruthenium and iridium complexes bearing dipyridylamine ligands . This type of catalyst was earlier identified as efficient transfer hydrogenation catalysts of ketones in water .…”
Section: Figurementioning
confidence: 99%
“…Recently,o ur group has been investigating the reduction of levulinic acid into g-valerolactone by using ruthenium and iridium complexes bearing dipyridylamine ligands. [10] This type of catalystw as earlier identified as efficient transfer hydrogenation catalysts of ketones in water. [11] In particular, we demonstrated that the transfer hydrogenation of levulinic acid with formic acid was proceeding essentially by hydrogenation resulting from av ery fast initial formic acid dehydrogenation under base-free conditions.…”
mentioning
confidence: 91%
See 1 more Smart Citation